Cutaneous manifestations of hypothyroidism: An observational study in a tertiary care center of Eastern India - Swastika Debbarma; Aniruddha Ghosh (Asian Journal of Medical Sciences, 2024)
Background: Changes in skin, hair, and nails may be initial manifestations of an underlying thyroid hormone deficiency. Symptomatic treatment of cutaneous manifestations without treatment of underlying hypothyroidism contributes to long-term morbidity in patients. Aims and Objectives: The aim of the study was to study the cutaneous manifestations and demographic profile of patients with hypothyroidism. Materials and Methods: We conducted a hospital-based cross-sectional study of 200 patients presenting with cutaneous changes in primary hypothyroidism for a period of 18 months. A detailed history, clinical examination, and relevant investigations were performed. Results: Out of 200 patients, cutaneous manifestations were more prevalent in the age group between 30 and 49 years. The ratio of male to female was 1.0:6.4. A family history of hypothyroidism was present in 34.5% of patients. The most common cutaneous features were alteration in skin texture (53.0%), dry skin (48.5%), generalized pruritus (42.5%), urticaria (17%), followed by pigmentation of the skin (34.5%), out of which vitiligo was 9.0%, melasma was 5.5%, and others were 20.0%. Other changes include xerosis (32.5%), eczematous disorder (13%), acquired palmoplantar keratoderma (11.5%), and brittle nails (3.5%). 39.5% had hair changes, out of which diffuse hair loss was 17.5%, coarse hair wa s 12%, alopecia areata was 4.5%, and lateral loss of eyebrows was 4.5%. Changes in the oral cavity and mucous membrane were present in 3.0% of the patients, which included lip vitiligo (1.5%), oral lichen planus (1%), and oral candidiasis (0.5%). Menstrual abnormalities were present in 50.84% of females. The percentage of hypothyroid patients who complained of easy fatigability, facial puffiness, cold intolerance, weight gain, constipation, neck swelling, hoarseness of voice, increased sleeping pattern, and non-pitting edema of feet were 38.5%, 36.5%, 26.0%, 23.5%, 17.0%, 9%, 8%, 7.5%, and 6.5%, respectively. Conclusion: Based on our study, it can be concluded that the presence of certain skin conditions, such as alteration in skin texture, dry skin, generalized pruritus, urticaria, skin pigmentation, and diffuse hair loss, may indicate the possibility of hypothyroidism. These cutaneous manifestations may occur earlier than the diagnosis of hypothyroidism through biochemical testing. Therefore, it is important to consider the possibility of hypothyroidism when examining patients with these skin conditions.